Komparasi Analisa Kinerja Mesh Interface Dan Bridge Interface Pada Wireless WDS Mesh Network - Arief Ikhwan Wicaksono; Rama Sahtyawan; Agung Priyanto (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Wireless mesh networking provides a solution to the problem of network distribution that has been constrained by cable networks and wireless networks that are not directly related to other wireless networks. Some of the advantages of wireless mesh technology include extended coverages, robustness, self-configuration, easy maintenance, and low cost. Based on the problems described in the previous paragraph, this research will analyze the performance of two wireless mesh distribution methods using several topology scenarios which will later be considered to affect the quality of network distribution WDS Mesh distribution methods that will be compared in this study are WDS Mesh with Mesh Interface, and WDS Mesh with Bridge Interface. Evaluation of the two methods will be conducted periodically to get the results of the analysis which will be used to do re-configuring to maximize the features and advantages of mesh technology in maintaining reliable network quality.